Impact of virtual modality on the training of physical education students: A post-pandemic study - Andri Velásquez-Salazar; Isolda Vergara-Santiago; Ronnie Videla Reyes; Valentín Mercado Hernández; Juan Díaz Labrin; Patricio Anacona Godoy (spdfharmony.com, 2025)
Background: The educational experience of Physical Education Pedagogy students during virtual learning highlighted structural tensions that significantly affected the quality of the training process. Aim: This study analyzed the relationship between class modality and training quality among Physical Education students at a Chilean university after an extended period of virtual classes. Method: A non-experimental quantitative approach was used with a correlational scope. The sample included 56 students (35 males and 21 females) who answered a questionnaire, and the data were analyzed using IBM SPSS Statistics software. Results: The chi-square test of independence (χ² (3) = 2.75, p = .432) revealed no significant differences by gender or regarding the return to in-person classes, indicating that students shared similar perceptions. Conclusion: The return to in-person learning was perceived by students as a process full of challenges for their professional development.